Teasing Out mm: Bilabial-Nasal Response Particles in Norwegian - Sbertoli-Nielsen, Paul (Norsk Lingvistisk Tidsskrift, 2023)
This article presents initial findings from the first systematic investigation of /2mm/, a disyllabic bilabial-nasal response particle pronounced with the specific high-low-high wave form of the East Norwegian ‘second tonal accent’. Estimated frequencies from three extensive corpora indicate /2mm/ as by far the most common bilabial-nasal particle in Norwegian, vastly outnumbering monosyllabic /m/ and disyllabic /mhm/ known from general (English based) literature. In spite of this, /2mm/ has remained largely underexamined, and is often not distinguished from /m/ or /mhm/ in neither transcription nor analysis of interactional work. I here consider alternatives for their distinct representation, and preliminarily analyze a collection of 420 cases in Norwegian, clustered around continuer work and agreement/acknowledgement, where they appear to do discrete social actions.